Tourist Preferences in Culinary during Covid-19 Pandemic in Bandung - Edwin Baharta; Suryana Heryawan Achmad; Astri Wulandari; Dandy Marcelino (Jurnal Kawistara, 2022)
Tourism is one of the areas that is badly affected by the Covid-19 pandemic and this includes culinary tourism. However, shifts in culinary preference during the pandemic also give a new life in culinary tourism. Bandung, one of Indonesia’s major tourist destination, shows a potential to develop further in its culinary tourism during the pandemic. This however requires a proper strategy through identifying the preferences of tourists in choosing culinary tourism during the pandemic. This research provides a knowledge base for culinary tourism business people regarding tourist preferences in a pandemic situation like today. Data about the preferences of tourists can help culinary tourism business people to develop the right strategy to serve tourists in future and can design the right policies and strategies to respond the expectations and desires of tourists, especially culinary tourism in Bandung. With a sample size of 400 respondents, this study is a descriptive quantitative study employing the conjoint analysis approach, which is the most popular methodology to analyzing tourist preferences. This research found that the possibilities of travelers preferences when travelling Bandung as culinary vacation spot in pandemic are as follows. The aspect of selecting culinary products based on tourist facilities is the preference of tourists in COVID-19 pandemic. Meanwhile, the location of culinary with consideration of easy access or reach becomes choice of tourists in pandemic, in addition to the important of health protocols the cleanliness of locations. Finally, the priority score analysis found that the culinary product selection element has the greatest importance level among the other features.